Correlation of Serodiagnosis with Morphological Verification of Cystic Echinococcosis, and the Association of Patients’ Blood Types with Echinococcus Invasion - Victorovich , Galyavin Alexey (South Eastern European Journal of Public Health, 2024)
A retrospective analysis was carried out in 110 patients with echinococcosis of the liver and lungs operated on in various hospitals of the Russian Federation, in whom the diagnosis of Cystic Echinococcosis was morphologically verified (intra-vitam). According to the study, clinical and epidemiological features were identified: main factors predisposing to echinococcus invasion, average duration of medical history before visiting a doctor, main clinical symptom complex; the correlation between the blood type of patients according to the AB0 system and the average European blood type was shown: significant differences were obtained for III(B) and IV(AB) blood types (p<0.05). In addition, the role of serological diagnosis of echinococcosis as an auxiliary, the effectiveness of which in the Russian Federation for cysts of type CE1 (according to the WHO-IWGE classification) reaches 71%.